SYNERGISTIC ANTIBACTERIAL EFFECTS OF CEFOTAXIME CAPPED METAL DOPED ZINC OXIDE NANOSTRUCTURES - Laraib, Saadia; Ali, Shahid; Sana Farooq Ahmed,; Bakhtawar Tufail,; Tanveer Ahmad, (Journal of Postgraduate Medical Institute, 2023)
Objectives: The study describes the synthesis of ZnO nanostructures doped with metals including Ca, Mg, Mn, Ag and Cu using a co-precipitation method. Methodology: The nanostructures were examined through Scanning Electron Microscopy (SEM) analysis and X-ray diffraction (XRD) assessment The antibacterial efficacy of these nanostructures was evaluated using a modified disk diffusion Kirby Bauer method. Results: Nanostructures displayed effective antimicrobial activity against a variety of bacterial strains. The most effective nanostructures were found to be those made with Ca-Cefotaxime and Ag-Cefotaxime doped ZnO. Conclusions: The study demonstrates that the combination of ZnO and Cefotaxime with different metal ions has an impact on the antibacterial activity against various bacterial strains. To the best of our knowledge, nanoparticles with cefotaxime have not been studied in the literature before. Further studies should investigate the mechanism of action.